Microscopic Agglutination Test for Diagnosis of Leptospirosis in Beef Cattle from Bantul and Kulon Progo - Susanti Susanti (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2015)
Leptospirosis is a zoonotic disease caused by bacterial infection, Leptospira interrogans. The bacteria usually infect many kinds of wild animals and humans as well. There was an extraordinary outbreak of leptospirosis in humans in Yogyakarta in 2011. Therefore, it is necessary to investigate the seroprevalences of leptospirosis in cows, especially in the districts of Bantul and Kulon Progo in order to determine the possible role(s) of the cows in the spread of leptospirosis among other animals and humans. In this research, the diagnostic method was conducted by using microscopic agglutination test (MAT). Bovine sera samples were obtained from several farms in some areas of the districts of Bantul and Kulonprogo. The MAT was conducted on 150 sera samples of cows from districts of Bantul and was on 200 samples from Kulonprogo. Seroprevalences of leptospirosis in the cows were 18.67 % ( 28/150 ) and 14.5% (29/200) from Bantul and Kulonprogro districts, respectively. Mostly, serovar tarassovi, hardjo, icterohemorrhagiae and batavia were detected in cows from both Bantul and Kulonprogo districts. Antibody titers were obtained ranged from 1:100, 1:400 and 1:1600.